HIV/AIDS and circumcision: lost in translation. Issue 12 (26th November 2010) - Fox, Marie; Thomson, Michael
Abstract : In April 2009 a Cochrane review was published assessing the effectiveness of male circumcision in preventing acquisition of HIV. It concluded that there was strong evidence that male circumcision, performed in a medical setting, reduces the acquisition of HIV by men engaging in heterosexual sex. Yet, importantly, the review noted that further research was required to assess the feasibility, desirability and cost-effectiveness of implementation within local contexts. This paper endorses the need for such research and suggests that, in its absence, it is premature to promote circumcision as a reliable strategy for combating HIV. Since articles in leading medical journals as well as the popular press continue to do so, scientific researchers should think carefully about how their conclusions may be translated both to policy makers and to a more general audience. The importance of addressing ethico-legal concerns that such trials may raise is highlighted. The understandable haste to find a solution to the HIV pandemic means that the promise offered by preliminary and specific research studies may be overstated. This may mean that ethical concerns are marginalised. Such haste may also obscure the need to be attentive to local cultural sensitivities, which vary from one African region to another, in formulating policy concerning circumcision.